The pyrrolidinoindoline alkaloid Psm2 inhibits platelet aggregation and thrombus formation by affecting PI3K/Akt signaling - SU Xing-li; SU Wen; WANG Ying; WANG Yue-hu; MING Xin; KONG Yi (Acta Pharmacologica Sinica; Vol 37, No 9 (September 2016): Acta Pharmacologica Sinica, 2017)
Aim: Psm2, one of the pyrrolidinoindoline alkaloids isolated from whole Selaginella moellendorffii plants, has shown a potent antiplatelet activity. In this study, we further evaluated the antiplatelet effects of Psm2, and elucidated the underlying mechanisms. Methods: Human platelet aggregation in vitro and rat platelet aggregation ex vivo were investigated. Agonist-induced platelet aggregation was measured using a light transmission aggregometer. The antithrombotic effects of Psm2 were evaluated in arteriovenous shunt thrombosis model in rats. To elucidate the mechanisms underlying the antiplatelet activity of Psm2, ELISAs, Western blotting and molecular docking were performed. The bleeding risk of Psm2 administration was assessed in a mouse tail cutting model, and the cytotoxicity of Psm2 was measured with MTT assay in EA.hy926 cells. Results: Psm2 dose-dependently inhibited human platelet aggregation induced by ADP, U4619, thrombin and collagen with IC50 values of 0.64, 0.37, 0.35 and 0.87 mg/mL, respectively. Psm2 (1, 3, 10 mg/kg) administered to rats significantly inhibited platelet aggregation ex vivo induced by ADP. Psm2 (1, 3, 10 mg/mL, iv) administered to rats with the A–V shunt dose-dependently decreased the thrombus formation. Psm2 inhibited platelet adhesion to fibrinogen and collagen with IC50 values of 84.5 and 96.5 mg/mL, respectively, but did not affect the binding of fibrinogen to GPIIb/IIIa. Furthermore, Psm2 inhibited AktSer473 phosphorylation, but did not affect MAPK signaling and Src kinase activation. Molecular docking showed that Psm2 bound to phosphatidylinositol 3-kinase β (PI3Kβ) with a binding free energy of −13.265 kcal/mol. In addition, Psm2 did not cause toxicity in EA.hy926 cells and produced only slight bleeding in a mouse tail cutting model. Conclusion: Psm2 inhibits platelet aggregation and thrombus formation by affecting PI3K/Akt signaling. Psm2 may be a lead compound or drug candidate that could be developed for the prevention or treatment of thrombotic diseases.